Methodology of Developing of Pupils' Lexical Competence Through Comics in Primary English Classes - Nishonova, Khurriyat (Indonesian Journal Publisher, 2024)
This article explores the methodology of developing pupils' lexical competence through the use of comics in primary English classes. Lexical competence, a key component of language proficiency, is crucial for young learners to effectively communicate and comprehend English. Comics offer a unique blend of visual and textual elements that can engage pupils and enhance their vocabulary acquisition. The article discusses the importance of lexical competence, the benefits of using comics in language learning, and a structured methodology for incorporating comics into vocabulary development activities. By following this methodology, educators can create a dynamic and interactive learning environment that fosters pupils' lexical competence.